Antipsychotic prescribing to patients diagnosed with dementia without a diagnosis of psychosis in the context of national guidance and drug safety warnings: longitudinal study in UK general practice - Stocks, S. Jill; Kontopantelis, Evangelos; Webb, Roger T.; Avery, Anthony J.; Burns, Alistair; Ashcroft, Darren M. (Springer, 2017)
Introduction: Policy interventions to address inappropriate prescribing of antipsychotic drugs to older people diagnosed with dementia are commonplace. In the UK, warnings were issued by the Medicines Healthcare products Regulatory Agency in 2004, 2009 and 2012 and the National Institute for Health and Care Excellence guidance was published in 2006. It is important to evaluate the impact of such interventions.